Komodifikasi Agama Dalam Iklan Bebas Gerah Dengan Vaseline Hijab Bright - Fajar Nursanto; Joko Sarjono; Agus Fatuh Widoyo (Pawarta: Journal of Communication and Da'wah, 2024)
The commercialization of religious values in advertising reflects the transformation of spiritual values into trading objects. To attract consumers, companies often use religious symbols to increase the appeal of their products. However, this raises controversy about the exploitation of religious values. This phenomenon creates tension between commercial purposes and the integrity of religious values. Research on the commodification of religious values in advertising is essential to understand market dynamics as well as the impact on the public's view of the religious value used for advertising. This research uses critical content analysis methods with observation collection and documentation techniques. To facilitate the research, the researchers also used the data analysis done with the semiotic analysis model of Charles Sanders Pierce. This method was chosen because it could help researchers to explore the meaning contained in the visual and symbolic elements of advertising, enriching an understanding of how messages are delivered and received by the audience. Analysis of Vaseline Hijab Bright's advertising revealed signs of practical commodification of religious values. There seems to be a transformation of the meaning of religious values into commercial exchange values, in which the concept of body serum that is considered safe from a religious point of view is combined with convenience from a commercial perspective. This process is reflected in advertising, where Vaseline modifies all Islamic values and shifts from functional values to exchange values in the context of its product.